ROMANIAN CHILDREN'S PERCEPTION OF DENTAL CAVITIES AND GINGIVAL BLEEDING IN CORRELATION WITH PERSONAL ORAL BEHAVIOURS - A CROSS SECTIONAL STUDY - Ștefana Popa; Bogdan Alexandru Dimitriu; Marina-Cristina Giurgiu; Anca Silvia Dumitriu; Stana Păunică; Brîndușa Florina Mocanu; Ștefania-Cristiana Colbu; Andreea Cristiana Didilescu (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study. The aim of the study was to evaluate the Romanian children's perception regarding 2 of the most common oral pathologies, dental caries and gingivitis in correlation with oral health behaviours. Methods. This was a cross-sectional study. The answers to 2 questionnaires distributed to children 12-15 years old from 2 schools in Bucharest, Romania were analyzed. One questionnaire included questions related to oral pathology, and the other to oral health maintenance behaviour. In our dental research study we made use of descriptive statistics in order to summarize continuous and categorical variables. The test used to examine relationship between children's perceptions and their behaviours was Roa-Scott chi-square test Results. All 137 children who participated in the study completed both questionnaires. Among them, 62% considered that a broken tooth is not a form of disease, but still 94.8% of them would go to the dentist. Regarding gingival bleeding, even if its presence as a sign of illness was not conclusive, most children (78.8%) considered that this sign requires medical attention. The frequency of sugar consumption in our study was low in 80.3% of children, and the frequency of brushing was more than once a day for 77.4% of subjects. Conclusions. Although most children perceived dental cavity as a disease and, gingival bleeding as not a sign of illness., there was a consensus regarding both conditions, that is, the necessity of dental treatment. Awareness of the need for dental treatment in case of signs for these two diseases is very important for promoting preventive dental programs for children.